Endoscopic vs. Microscopic Transsphenoidal Surgery for the Treatment of Pituitary Adenoma: A Meta-Analysis - Chen, Jia; Liu, Hongyan; Man, Siliang; Liu, Geng; Li, Quan; Zuo, Qingyao; Huo, Lili; Li, Wei; Deng, Wei (Frontiers in Surgery, 2022)
Purpose Currently, endoscopic transsphenoidal surgery (ETS) and microscopic transsphenoidal surgery (MTS) are commonly applied treatments for patients with pituitary adenomas. This meta-analysis was conducted to evaluate the efficacy and safety of ETS and MTS for these patients. Methods A computer search of Pubmed, Embase, Cochrane library, Web of Science, and Google Scholar databases was conducted for studies investigating ETS and MTS for patients with pituitary adenomas. The deadline is March 01, 2021. RevMan5.1 software was used to complete this meta-analysis after literature screening, data extraction, and literature quality evaluation. Results A total of 37 studies including 5,591 patients were included. There was no significant difference in gross tumor removal (GTR) and hormone-excess secretion remission (HES remission) between two groups [RR = 1.10, 95% CI (0.99–1.22), P = 0.07; RR = 1.09, 95% CI (1.00–1.20), P = 0.05]. ETS was associated with lower incidence of diabetes insipidus (DI) [RR = 0.71, 95% CI (0.58–0.87), P = 0.0008], hypothyroidism [RR = 0.64, 95% CI (0.47–0.89), P = 0.007], and septal perforation [RR = 0.32, 95% CI (0.13–0.79), P = 0.01] than those with MTS. Conclusion This meta-analysis indicated that ETS cannot significantly improve GTR and HES remission. However, ETS could reduce the incidence of DI, hypothyroidism, and septal perforation without increasing the rate of other complications. Systematic Review Registration https://www.crd.york.ac.uk/prospero/#myprospero, identifier: CRD42021241217.